Isolation and characterization of a temperature-sensitive lethal mutant of Salmonella typhimurium that is conditionally defective in 3-deoxy-D-manno-octulosonate-8-phosphate synthesis. - Rick, P D (1982)
A new mutant of Salmonella typhimurium was isolated which possesses a temperature-sensitive defect in the synthesis of 3-deoxy-D-manno-octulosonic acid. The defect in 3-deoxy-D-manno-octulosonic acid synthesis is due to a temperature-sensitive 3-deoxy-D-manno-octulosonate-8-phosphate synthetase, and the mutant accumulates an incomplete lipid A under nonpermissive conditions. Evidence is presented which indicates that the incomplete lipid A molecule is most likely identical in structure to the lipid A precursor synthesized by previously characterized mutants conditionally defective in 3-deoxy-D-manno-octulosonic acid synthesis. However, unlike related mutants which undergo growth stasis under nonpermissive conditions, the accumulation of lipid A precursor in the new mutant results in cell death at elevated temperatures.